Chest Trauma Evaluation and Outcome of Management in a Tertiary Hospital - One Year Experience (Journal of Surgical Sciences, 2020)
Background: Chest trauma is responsible for 50% of deaths due to trauma. This kind of death usually occurs immediately after the trauma has occurred. Various therapeutic options have been reported for management of chest injuries like clinical observation, thoracocentesis, tube thoracostomy and open thoracotomy. Objective: To observe the pattern and outcome of management in chest traumaMethods: This is an observational study carried out in Casualty department of Chittagong Medical College Hospital (CMCH), Chittagong, between April 2015 to March 2016. Our study was included all patients, both sexes, following chest injury at Casualty units of Chittagong Medical College Hospital. All the data were recorded through the preformed data collection sheet and analyzed. Result: The mean age was found 37.7±18.1 years with range from 12 to 80 years. Male female ratio was 11.8:1. The mean time elapsed after trauma was found 6.1±3.1 hours with range from 1 to 72 hours. Almost one third (35.7%) patients was affecting road traffic accident followed by 42(27.3%) assault, 35(22.7%) stab injury, 15(9.7%) fall and 7(4.5%) gun shot . More than three fourth (80.5%) patients were managed by tube thoracostomy followed by 28(18.2%) observation and 2(1.3%) ventilatory support. No thoracotomy was done in emergency department. 42(27.2%) patients was found open pneumothorax followed by 41(26.6%) rib fracture, 31(20.1%) haemopneumothorax, 14(9%) simple pneumothorax, 12(7.8%) haemothorax, 6(3.9%) chest wall injury, 5(3.2%) tension pneumothorax, and 3(1.9%) flail chest. About the side of tube 60(39.0%) patients were given tube on left side followed by 57(37.0%) patients on right side, 9(5.8%) patients on both (left & right) side and 28(18.2%) patients needed no tube. Regarding the complications, 13(30%) patients had persistent haemothorax followed by 12(29%)tubes were placed outside triangle of safety, 6(13.9%) tubes were kinked, 6(13.9%) patients developed port side infection, 2(4.5%)tube was placed too shallow, 2(4.5%) patients developed empyema thoracis and 2(4.5%) patients developed bronchopleural fistula. The mean ICT removal information was found 8.8±3.6 days with range from 4 to 18 days. Reinsertion of ICT was done in 6(4.7%) patients. More than two third (68.2%) patients were recovered well, 43(27.9%) patients developed complication and 6(3.9%)patients died. More than two third (66.9%) patients had length of hospital stay 11-20 days.Conclusion: Most of the patients were in 3rd decade and male predominant. Road traffic accident and tube thoracostomy were more common. Open pneumothorax, rib fracture and haemopneumothorax were commonest injuries. Nearly one third of the patients had developed complications. Re-insertion of ICT needed almost five percent and death almost four percent.Journal of Surgical Sciences (2018) Vol. 22 (2) : 110-117